Cytotoxicity of the effector protein BteA was attenuated in Bordetella pertussis by insertion of an alanine residue - Bayram, Jan; Malcova, Ivana; Sinkovec, Larisa; Holubova, Jana; Streparola, Gaia; Jurnecka, David; Kucera, Jan; Sedlacek, Radislav; Sebo, Peter; Kamanova, Jana (PLoS pathogens, 2020)
Bordetella bronchiseptica and Bordetella pertussis are closely related respiratory pathogens that evolved from a common bacterial ancestor. While B. bronchiseptica has an environmental reservoir and mostly establishes chronic infections in a broad range of mammals, B. pertussis is a human-specific pathogen causing acute pulmonary pertussis in infants and whooping cough illness in older humans. Both species employ a type III secretion system (T3SS) to inject a cytotoxic BteA effector protein into host cells. However, compared to the high BteA-mediated cytotoxicity of B. bronchiseptica, the cytotoxicity induced by B. pertussis BteA (Bp BteA) appears to be quite low and this has been attributed to the reduced T3SS gene expression in B. pertussis. We show that the presence of an alanine residue inserted at position 503 (A503) of Bp BteA accounts for its strongly attenuated cytotoxic potency. The deletion of A503 from Bp BteA greatly enhanced the cytotoxic activity of B. pertussis B1917 on mammalian HeLa cells and expression of Bp BteAΔA503 was highly toxic to Saccharomyces cerevisiae cells. Vice versa, insertion of A503 into B. bronchiseptica BteA (Bb BteA) strongly decreased its cytotoxicity to yeast and HeLa cells. Moreover, the production of Bp BteAΔA503 increased virulence of B. pertussis B1917 in the mouse model of intranasal infection (reduced LD50) but yielded less inflammatory pathology in infected mouse lungs at sublethal infectious doses. This suggests that A503 insertion in the T3SS effector Bp BteA may represent an evolutionary adaptation that fine-tunes B. pertussis virulence and host immune response.
Keywords: Humans; HeLa buňky; sekreční systém typu III; Female; mutace; Virulence; myši inbrední BALB C; lidé; zvířata; Bordetella pertussis; virulence; myši; bakteriální proteiny; pertuse; regulace genové exprese u bakterií; Mice; ženské pohlaví; Type III Secretion Systems; HeLa Cells; Alanine; alanin; Gene Expression Regulation, Bacterial; Bacterial Proteins; Whooping Cough; Animals; Mutation; Mice, Inbred BALB C